Occurrence of Agaricomycetes (Basidiomycota) in two areas of the Amazon Forest in the state of Acre, Brazil - Santos, Geyse Souza; Souza, Bruno Jhosef Freires de; Lima, Yara de Moura Magalhães; Carvalho, Clarice Maia (Acta Scientiarum. Biological Sciences, 2025)
Agaricomycetes are macroscopic fungi popularly known as mushrooms and wooden ears. Few studies have documented the diversity of Agaricomycetes in the state of Acre, Brazil. Thus, the objective of this work was to describe the occurrence and type of substrate of Agaricomycetes in two areas of the Amazon Forest in the State of Acre, Brazil. Collections were made at the UFAC Parque Zoobotânico and at the Fazenda Experimental Catuaba. The Agaricomycetes were collected in pre-existing trails, the fungal basidiome was removed from the substrate with the aid of a penknife and packed in paper bags and plastic boxes. In order to identify the Agaricomycetes, the macroscopic and microscopic characteristics were observed with the aid of specific literature, and specimens of all collected material were prepared. A total of 100 Agaricomycetes were collected, of which 86% of the specimens were identified, distributed across 21 families, 37 genera, and 18 species, while the remaining 14% were kept at the order taxonomic level. The orders observed were Agaricales (82%), Polyporales (11%), Geastrales (2%), Phallales (2%), Auriculariales (1%), Hymenochaetales (1%), and Russulales (1%). This study describes the Agaricomycetes found in two areas of the Amazon Rainforest in the state of Acre, expanding knowledge on fungal biodiversity in the Brazilian Amazon. Additionally, it records for the first time the occurrence of the species Filoboletus gracilis, Xeromphalina tenuipes, Lentinula raphanica, Pleurotus djamor, and Poromycena cf. violacella in state of Acre, Brazil.